The effectiveness of natural ventilation in low cost houses (Single, double storey and renovated terraced houses) / Nurhasyimah Ishak - Ishak, Nurhasyimah (Faculty of Architecture , Planning and Surveying, 2002)
For the past few decades, Malaysia has been housing its people to support the growing population. It is expected to reach 32 million in the next two decades.To fulfill the demand, the government has taken the action of increasing the number of housing needs for the people, including the low income group that includes low cost houses.It is the government as well as other related party’s responsibility to provide comfortable, sound living quarters for the people. This includes providing a better ventilation design. Many have complained about the unbearable heat they have to put up with everyday. This has drawn few attentions but no action has yet been taken to improve the condition despite researches that have been done.Overall, the objective of this dissertation is to highlight the problems caused by inadequate natural ventilation and how it can be optimized through planning and design of openings, materials, etc.The study is focused on low cost terraced houses in Shah Alam.Questionnaires will be distributed to 50 respondents to gather data and finally make an analysis on the findings.